Unsung women heroes in Indian freedom struggle: An acknowledgement - Sharma, Urmila (2014)
This paper is all about unsung women heroes in Indian Freedom Struggle with specific reference to Rajas than State in India.It is an effort by the author to acknowledge those women heroes who participated in the Indian Freedom Movement even though all of them belong to very poor and mediocre family background.Still they have shown courage and confidence to come forward and made a significant contribution in the Freedom Movement and Bijolia Kisan Andolan gainst Jagirdari Pratha started in Rajasthan in the leadership of Vijay Singh Pathik, Manikaya Lal Verma and Sadhu Sita Ram.They have made women class awakened for their rights against the royal state. In future, this development contributed in producing many women leaders in Rajasthan State.In this paper the author is going to present unsung stories of women heroes like Ganga Bai, Nayarani Devi Verma, Bharti Devi Vajpayee, Santa Trivedi, Smt. Gorya Devi, Smt. Anjana Deve Choudhary, Shakuntala Trivedi, Bhagvati Devi, Durga Devi, Ratan Shastri, Nagendra Bala, who participated in the Indian Freedom Struggle and left their footprints of their sacrifice and success in getting freedom in India. Briefly mentioning the contribution of one out of eleven women like Narayani Devi Verma inspired by Bijolia Andolan, who had worked for women education and social work.In 1942, she went to jail in Parjamandal Movement.Later on, she established a women center in Bhilwara to make women aware about their rights.In my view it is a great effort to present the biography of all women unsung heroes and acknowledging their tiresome efforts, sacrifice and dedication in the Indian Freedom Struggle.On behalf of all the historians, I personally acknowledge their presence and contribution and pay a salute and tribute to them.